Willingness to pay for flexibility at the workplace for people with diabetes and chronic disease: a discrete choice experiment in a population of workers in Denmark - Kristoffer Panduro Madsen; Bryan Cleal; Kasper Olesen; Lise Hagelund; Ingrid Willaing (BMC, 2019)
Abstract Background The number of people of working age suffering from chronic disease is increasing. Chronic diseases such as diabetes can cause negative work-related consequences in the form of early retirement or absenteeism. Providing flexible workplace accommodations may enable the person with diabetes to retain their position in the labor market. However, the successfulness of such accommodations depends largely on the perceptions of those not suffering from diabetes. The purpose of this study was to examine preferences of a population of workers in Denmark for flexibility at the workplace, for people with diabetes and for people with chronic disease in general, measured as their willingness to pay (WTP). Methods Respondents were drawn from online panels and randomized to answer an online survey regarding flexibility at the workplace for people with diabetes or chronic disease in general. One thousand one hundred and three respondents were included in the analysis. Based on discrete choice experiments included in the survey, we analyzed WTP for five flexibility attributes: part-time, customizing job description, additional break with pay and time off for medical visits with and without pay. We further examined perceptions of the employer's responsibility to ensure workplace flexibility for five different specific chronic diseases including diabetes. Finally, we analyzed differences in WTP for flexibility across subgroups. Results Respondents' WTP was significantly higher for chronic disease in general compared to diabetes for the possibility of part-time (81€/month vs. 47€/month, p < 0.001) and customizing job description (58€/month vs. 41€/month, p = 0.018) attributes, as well as for the overall average (49€/month vs. 36€/month, p = 0.008). Ensuring workplace flexibility for patients with a specific chronic disease other than diabetes (cancer, heart disease, arthritis and COPD) was to a higher degree considered a responsibility of the employer. Average WTP for flexibility varied across subgroups, consistently yielding a larger amount for chronic disease in general. Conclusions The population examined in this study are willing to pay less for flexibility at the workplace for people with diabetes compared to people with chronic disease in general. This finding was evident in terms of specific flexibility attributes and on average across subgroups.